THE EFFECT OF READING PURPOSE ON READING COMPREHENSION OF GRADE XII STUDENTS OF MADRASAH ALYAH DINIAH PUTRI RIAU - Missi Tri Astuti; Mei Lyna Girsang (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2022)
The effect of reading purpose on the reading comprehension was studied at Madrasah Alyah Diniyah Riau.The aim was to know and identify the effect of reading purpose on the reading comprehension of 12th-grade students 2021 – 2022 Academic Year at Madrasah Alyah Diniyah Riau . A mixed-method approach and quantitative and qualitative of an ex-post-facto study was applied. The 42 of 12th-grade IPA and IPS students of Madrasah Alyah Diniyah Riau 2021–2022 academic year were taken as sample by using the purposive sampling technique. The instrument of questionnaire and a test of reading comprehension were used to collect the data. Hypothesis testing (t-test) were used to analyse the collected data. From the analysis result it was found that the t-value = 277,543 > t-table 1,689 with a sig. value of 0,000 < 0.05,it can be interpreted that reading purpose affected the reading comprehension of Grade XII students 2021 – 2022 Academic Year of Madrasah Alyah Diniyah Riau